2021
DOI: 10.2147/idr.s320024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characteristics Based on Whole Genome Sequencing of Mycobacterium tuberculosis Resistant to Four Anti-Tuberculosis Drugs from Southern Xinjiang, China

Abstract: Drug-resistant tuberculosis is a major public health problem, especially in the southern region of Xinjiang, China; however, there is little information regarding drug resistance profiles and mechanism of Mycobacterium tuberculosis in this area. The aim of this study was to determine the prevalence and molecular characteristics of M. tuberculosis resistant to four anti-tuberculosis drugs from this area. Methods: Three hundred and forty-six isolates from the southern region of Xinjiang, China were included and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(82 reference statements)
0
9
1
Order By: Relevance
“… 28 The katG Ser140Asn and ahpC −54C>T mutations were not associated with isoniazid resistance in our study; however, they were found in isoniazid-resistant strains in Anwaierjiang et al’s study. 29 The sample size of our study was small, meaning that it could not fully confirm the function of many mutation sites. Prothionamide, an analog of ethionamide, is an orally available second-line agent frequently incorporated into regimens for MDR-TB.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“… 28 The katG Ser140Asn and ahpC −54C>T mutations were not associated with isoniazid resistance in our study; however, they were found in isoniazid-resistant strains in Anwaierjiang et al’s study. 29 The sample size of our study was small, meaning that it could not fully confirm the function of many mutation sites. Prothionamide, an analog of ethionamide, is an orally available second-line agent frequently incorporated into regimens for MDR-TB.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study, rpoB Leu430Pro was found in rifampicin-resistant strains. 29 This mutation may be related to the activity of the strain. Studies have shown that rpoB expression is upregulated in XDR-TB strains that are exposed to rifampicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA of M. tuberculosis isolates was extracted using the CTAB method for sequencing as previously described. 23 , 24 DNA libraries were constructed with genomic DNA using kits provided by Illumina according to the manufacturer’s instructions. The average sequencing depth of the genome is 124.8, and the coverage is 99.3%.…”
Section: Methodsmentioning
confidence: 99%
“…It may also be affected by differences in host immunity and external living environment, resulting in diversity in the distribution of M.tb lineages and sub-lineages in different geographical regions [ 10 12 ]. At present, M.tb lineages in the Kashgar prefecture and the Xinjiang region are primarily detected by traditional typing methods; however, there is insufficient research on M.tb lineage in terms of whole-genome SNP [ 13 ].…”
Section: Introductionmentioning
confidence: 99%